Islamic Banking Sustainability in Indonesia - Malini, Helma (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
Corporate governance exists to increase and maintain shareholder value. On this basis, corporate governance is argued to be vital to any company's long-term viability. To determine how transparency and accountability affected the Islamic banking sector's long-term viability. The study was guided by three theories: agency theory, stewardship theory, and stakeholder theory. This study is quantitative. It is used in quantitative research to generate numerical data or data that can be transformed into statistics. Transparency, accountability, justice, and responsibility are all important factors in the study's findings. Transparency and accountability appear to have a significant impact on the banking industry's long-term viability. To achieve sustainability, Islamic banks in Indonesia should strictly enforce transparency in all operations and worker activities.